HUKUM EKONOMI SEBAGAI PANGLIMA PEMBANGUNAN - Purwanto Purwanto (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2020)
The law is supreme that must be obeyed by every citizen and must be upheld by the State in the context of national, state and community life. The constitutional foundation provides an understanding that the administration of the Indonesian State is based on the concept of law. The role of law in the reform era in all fields of science is concrete evidence, essentially the life of the community requires a set of legal rules that can always maintain order and furthermore provide legal certainty, usefulness and justice. The problem to be discussed in this paper the author wants to know "How the Role of Economic Law as the Commander in Chief of Development" Economic development must be done through a strong legal foundation. Economics is the backbone of people's welfare, and science is the pillar of national progress, but the law is the institution that ultimately determines how the people's welfare can be enjoyed equally, and how social justice can be realized in people's lives, and how scientific progress and technology can bring progress to the people.